Factors influencing newspaper readers buying intention / Nor Afida Abu Zaharin - Abu Zaharin, Nor Afida (Faculty of Business and Management, 2008)
The primary objective for this research, title the factors influencing newspaper readers buying intention basically to focus on the reason, why readers prefer one newspaper as compared to other newspaper. Therefore, it gives ideas to researcher to obtain information based on four factors which are content, price, contest and size. Hopefully, at the end of the findings, researcher can discover the most significant relationship between factors with newspaper readers buying intention. In this research, researcher use correlation bivariate. Researcher thinks this method suitable in order to identify simple relationship between dependent and independent variables. Researcher use descriptive method whereby it describes both variables. At the end of research findings, I shows that only content have significant relationship as compared to other variables.